Complete defluorination of perfluorooctanoic acid (PFOA) by ultrasonic pyrolysis towards zero fluoro-pollution. (15th May 2023) - Xiong, Xingaoyuan; Shang, Yanan; Bai, Lu; Luo, Shuang; Seviour, Thomas William; Guo, Zheng; Ottosen, Lars D.M.; Wei, Zongsu
Highlights: 100% defluorination of PFOA after 4 h of ultrasound (US) treatment alone. Persulfate (PS) addition, however, suppressed defluorination. PS competes with PFOA to partitioning onto the bubble-water interface. Sulfate (SO4 – ) and hydroxyl ( OH) radicals did not defluorinate PFOA. PFOA vaporizes at interface, enters the bubble, and is cleaved by pyrolysis. Abstract: Advanced oxidation/reduction of PFAS is challenged and concerned by the formation of toxic, short-chain intermediates during water treatments. In this study, we investigated the complete defluorination of PFOA by ultrasound/persulfate (US/PS) with harmless end-products of CO2, H2 O, and F ‒ ions. We observed 100% defluorination after 4 h of US treatment alone with a power input of 900 W. PS addition, however, suppressed defluorination. We demonstrated by kinetics-fitted Langmuir-type adsorption modeling, the added PS increased competition with PFOA for adsorption sites on the bubble-water interface where radical oxidation and pyrolysis may occur. Providing sulfate (SO4 – ) and hydroxyl ( OH) radicals by means other than US did not defluorinate PFOA, indicating that pyrolysis likely contributes to the high defluorination performance. Bond dissociation energies for CC and CF were independent of pressure but decreased at elevated temperatures within cavitation bubbles ( i.e., 5000 K) favoring the pyrolysis reactions. Furthermore, bond length calculations indicated that PFOA cleavage only begins to occur at temperatures in excess of those generated at the bubble interface (i.e., >1500 K) at the femtosecond level. This suggests that PFOA vaporizes or injects by nanodrops upon attachment to the cavitation bubble, enters the bubble, and is then cleaved within the bubble by pyrolysis. Our research in low-frequency ultrasonic horn system challenges the previous founding that defluorination of PFOA initiates and occurs at the bubble-water interface. We describe here that supplementing US-based processes with complementary treatments may have undesired effects on the efficacy of US. The mechanistic insights will further promote the implementation of US technology for PFAS treatment in achieving the zero fluoro-pollution goal. Graphic abstract: Image, graphical abstract